IMPLEMENTATION OF FORMATIVE ASSESSMENT IN KURIKULUM MERDEKA BY ENGLISH TEACHER OF SMPK ADISUCIPTO PENFUI - NONING, YULIANA A.; FELIX, TANS; BERA, LAURENSIUS K. (Postgraduate School, Universitas Nusa Cendana, 2023)
Learning assessment is an important part of the Implementation of Kurikulum Merdeka. This is because assessment is valuable for facilitating learning, providing comprehensive information about students, knowing students’ learning progress, and as feedback on the learning process both from the teacher's side and from the students’ side. Conducting an assessment helps teachers to determine the next steps to be taken in order to improve the quality of learning. In implementing learning assessment, teachers should understand the principles of assessment in Kurikulum Merdeka. This research aims at describing how English teachers implement learning assessment in the class at describing the level of English learning assessment implemented by English teacher of Sekolah Penggerak SMPK Adisucipto Penfui. The results of this research are (1) the implementation of learning assessment has been done well because English teachers are able to implement most of the assessment principles in learning activities in the class, (2) Even though most of the assessment principles have been implemented properly, there are a small number of assessment principles that have not been implemented optimally such as self-assessments, peer assessment, self-reflection and providing peer feedback.